PROBLEMATIC ISSUES OF INNOVATION ACTIVITY IN UKRAINE: THE TAX ASPECT (INNOVATIVE ECONOMY, 2020)
Chzhyshyn O.I. PROBLEMATIC ISSUES OF INNOVATION ACTIVITY IN UKRAINE: THE TAX ASPECTPurpose. The aim of the article is the determination of directions for activation of innovation activity of Ukrainian enterprises and implementation of successful market reforms taking into account the experience of developed countries on preferential taxation of innovation activity.Methodology of research. The modern general scientific and special methods of economic research are used in the article, in particular: system approach – when studying economic ties in the system of management of innovative processes of enterprises; statistical analysis – in determining the dynamics, structure and impact of the development of enterprise innovation; dialectical, abstract and logical – when conducting theoretical generalizations and forming conclusions.Findings. It has been established that for the development of entrepreneurship it is necessary to have an appropriate financial base, which, in market conditions, is expedient to form not only through direct financing methods, but also through the use of indirect levers such as taxes. It has been determined that tax incentives for entrepreneurship in Ukraine during all years of independence were not sufficiently effective and, consequently, did not bring the expected results.Originality. Attracting advanced foreign experience to stimulate tax incentives for entrepreneurship development is now a particularly important problem requiring systematic study and resolution, introducing a stimulating model of income tax with an appropriate mechanism for its administration. As an example of European countries, introduce a differential rate for profit, which reinvested in the operating and investment activities of the entity.Practical significance. The introduction of a differentiated rate of return will ensure the expansion of sources of funding not only the study and implementation of innovations according to the example of European countries, but also the training of specialists, which in turn will lead to a qualitatively new organization of the relationship between innovation structures, enterprises and government authorities.Key words: innovation activity; taxation; market; profit; entrepreneurship.
Keywords: Key words; innovation activity; taxation; market; profit; entrepreneurship.